Environmental education as a priority in education of a contemporary man - Buchcic, Elżbieta (Studia Ecologiae et Bioethicae, 2020)
People never stop learning and developing their skills. Education is associated with different spheres and different moments of people's lives. The learning process is mainly linked with schools, however, we should not underestimate that process which takes place outside schools as well. What we have learned, contributes, to a great extent, to what sort of people we are. The more we know, the more aware of the nearby World development, the more aware of phenomena understanding, phenomena that take place around us and, therefore, allow us to participate in all society activities.